Cost-effectiveness analysis of Daclatasvir/Sofosbuvir for the treatment of the HCV patients failed after the first line with second generation of DAAs in Italy. (4th May 2019) - Ruggeri, M.; Rolli, F. R.; Kondili, L. A.; Drago, C.; De Solda, F.; Nappi, C.; Cicchetti, A.
ABSTRACT: Background : Daclatasvir (DCV) combinated with Sofosbuvir (SOF) has shown good efficacy and safety profile for HCV patients. The aim was to evaluate the cost-effectiveness of DCV/SOF regimen versus HCV alternative treatments for patients who failed to achieve the SVR12 after a first DAA treatment from Italian perspective (PITER cohort). Methods : A Markov model of HCV chronically infected patients was used to develop two scenarios: 1) DCV+ SOF versus Ledipasvir (LDV)+ SOF in Genotype (Gt)1 and Gt4; 2) DCV+ SOF versus no retreatment option in Gt1, Gt3, and Gt4. The percentage of patients who failed the first line with SOF/Simeprevir/Ribavirin (RBV) or SOF/RBV and were retreated or not according to evidences from PITER cohort, were used to populate the model. HCV resources consumption and SVR rates were quantified using PITER data. Transition probabilities and utility rates were derived from the literature. The outcomes were expressed in terms of Quality adjusted life years (QALYs). Probabilistic sensitivity analysis (PSA) was performed considering a cost-effectiveness threshold of € 30, 000/QALY. Results : In the base-case analysis, DCV+ SOF represents a cost-effectiveness therapy with ICERs lower than the threshold. The PSA showed robust results, ICERs remain below the threshold in 94% and 99% simulations in Scenario 1 and 2, respectively.